(untitled) (Journal of Applied Oral Science, 2013)
OBJECTIVE: The shear bond strengths of two hard chairside reline resin materials and an auto-polymerizing denture base resin material to cast Ti and a Co-Cr alloy treated using four conditioning methods were investigated. MATERIAL AND METHODS: Disk specimens (diameter 10 mm and thickness 2.5 mm) were cast from pure Ti and Co-Cr alloy. The specimens were wet-ground to a final surface finish of 600 grit, air-dried, and treated with the following bonding systems: 1) air-abraded with 50-70-µm grain alumina (CON); 2) 1) + conditioned with a primer, including an acidic phosphonoacetate monomer (MHPA); 3) 1) + conditioned with a primer including a diphosphate monomer (MDP); 4) treated with a tribochemical system. Three resin materials were applied to each metal specimen. Shear bond strengths were determined before and after 10,000 thermocycles. RESULTS: The strengths decreased after thermocycling for all combinations. Among the resin materials assessed, the denture base material showed significantly (p